Inventory Productivity and Stock Returns in Manufacturing Networks - Agrawal, Deepak; Osadchiy, Nikolay (Manufacturing and Service Operations Management, 2024)
Problem definition: We provide a novel, supply network-based perspective on inventory productivity and incentives for its improvement. Methodology/results: Using data from 2003 to 2019, we find that inventory productivity is lower materially and statistically for firms located upstream in the supply network, and higher for high degree and more central firms. Firms with high inventory productivity show high equity valuations and abnormal returns, with both valuations and abnormal returns amplified for upstream, low degree, and peripheral firms. Moreover, the difference in valuations and abnormal returns between best and worst performing firms is greater upstream, suggesting that financial markets offer outsized rewards for improving inventory productivity to upstream firms. Managerial implications: We show that the information about firm’s upstreamness and centrality in the supply network is a valuable predictor of its inventory productivity and financial performance. Our methods for evaluating upstreamness are useful for that purpose. For operations managers and firm executives, our results highlight strong incentives for inventory productivity improvement upstream in the supply network. For investors, we show that supply network position data can sharpen inventory-based arbitrage opportunities. Supplemental Material: The online appendix is available at https://doi.org/10.1287/msom.2022.0229 .